Outcome analysis of laparoscopic cholecystectomy in patients 65 years and older [Yaşi 65 ve daha üzerinde olan hastalarda laparoskopik kolesistektominin analiz sonuçlari] - (:unkn) unknown (AVES, 2012)
Purpose: To evaluate the incidence of morbidity and mortality observed after laparoscopic cholecystectomy performed on patients aged ≥65 years. Patients and Methods: Medical records of 420 patients aged ≥65 years, who underwent laparoscopic cholecystectomy were retrospectively evaluated Results: Three hundred and four women and 116 men were included (mean age, 68.85±3.34 years) in this study. Indications for surgery were chronic cholecystitis in 352 (83.9%) patients, acute cholecystitis in 48 (11.4%) patients, cholecystocholedocholithiasis in 12 (2.8%) patients, and biliary pancreatitis in eight (1.9%) patients. American Society of Anesthesiologists score in 364 patients (86.6%) was II or III. In 20 patients (4.7%), conversion to laparotomy was required. Postoperative complications were observed in 48 patients (11.4%), with wound infection being the most common (4.7%). Mortality occurred in 4 (1%) patients. The frequency of postoperative complications was higher and the length of hospital stay was longer in patients with an American Society of Anesthesiologists score of III or IV when compared to those with an American Society of Anesthesiologists score of I or II (p<0.05). Conclusion: Advanced age is not a contraindication for laparoscopic cholecystectomy and laparoscopic cholecystectomy can be safely performed in elderly patients. However, the incidence of postoperative complications and length of hospital stay increase with higher American Society of Anesthesiologists score.
Keywords: Elderly patient; Laparoscopic cholecystectomy